Pengaruh Expressive Writing Terhadap Penurunan Kecemasan Pada Mahasiswa Di Universitas Nusa Cendana Kupang - Santos, Yosefine Gardiella Dos; Millanyani, Heppy (Jurnal Inovasi Global, 2025)
Students are one of the groups that are vulnerable to stress and anxiety. Academic pressure, social demands, and the transition from adolescence to adulthood often cause significant psychological burdens. Anxiety that is not managed properly can have a negative impact on mental health, can affect concentration, academic performance, and overall quality of life. One of the methods used in cognitive psychotherapy that is used as a form of intervention in reducing anxiety in students is expressive writing therapy. This study aims to determine the effect of expressive writing on reducing anxiety in students and to determine the difference in the effect of expressive writing between the experimental group and the control group. This study used a quasi-experimental design research design using the Nonequivalent control group design approach. Based on the results of the repeated measure ANOVA test because the data is normally distributed. The results showed no significant difference between the pre- test and post-test averages in both groups with a p value within subjects = 0.322 and a p value between subjects = 0.890 (p> 0.05). The results of this study explain that the high dropout rate of participants from the initial 65 participants and those who followed the intervention in full amounted to 6 participants indicating a tendency for students to experience anxiety but are reluctant to follow psychological intervention and it is important to pay attention to external factors of the participants such as the environment and family as significant others that can influence participants because it will have an impact on the therapy itself.